Attributes to high-risk locations for road accidents at inter-urban expressway / Sharifah Zuraidah Syed Abdul Jalil …[et al.] - Syed Abdul Jalil, Sharifah Zuraidah; Shariff, S. Sarifah Radiah; Sulaiman, Saiful Aman; Mohd Wazir, Hanafi (Universiti Teknologi MARA, 2023)
Road accidents occurred everywhere along the expressway, especially at the inter-urban expressway, due to its high accessibility to wide-ranging highway networks. This study uses dataset from Shah Alam Expressway from 2013 to 2017 to determine the pattern of road accidents which includes the identification of high-risk locations at the expressway as well as the attributes to the accidents at those locations. In order to determine the high-risk location, the weightage point method and accident crash frequency method have been adopted. From the two methods applied, three popular identical sites have been identified as high-risk locations at both the westbound and eastbound. For the west bound, segments 19, 46 and 63 are considered as high risk whereas for the east bound, the high-risk locations are at segments 19, 46 and 60. Most of the accidents at the high-risk locations for west and east bounds caused no injury to road users and happened during daytime. Appropriate countermeasures should be done by local authorities in order to reduce accidents at the above-mentioned area. However, special countermeasures should be considered for segments 8, 28, 31 and 32 at the west bound whereby road accidents frequently happened during nighttime at these locations. On the other hand, a special scheme and countermeasure can be implemented for segment 46 at the eastbound where motorcyclists played a major involvement in road accidents at this location. Future research may consider applying some spatial statistics for detailed analysis to the accident dataset.